2018
DOI: 10.1002/art.40472
|View full text |Cite
|
Sign up to set email alerts
|

U‐Shaped Association Between Serum Uric Acid Level and Risk of Mortality

Abstract: In this large cohort study of men and women, both low and high uric acid levels were predictive of increased mortality, supporting a U-shaped association between serum uric acid levels and adverse health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
122
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 60 publications
(74 reference statements)
10
122
4
2
Order By: Relevance
“…Moreover, a similar trend was observed for cardiovascular mortality in both men and women, indicating the different threshold values of uric acid levels for mortality among men and women. Some previous studies reported the sex-specific threshold values of uric acid for all-cause mortality: uric acid levels ≥8.5 mg/dL in a male population in Japan (n = 49,413) 17 and Korea (n = 207,167) 11 and ≥7.5 mg/ dL in a female population in Korea (n = 167,996) 11 . The current study revealed that the threshold values of uric acid levels for all-cause mortality (≥7.0 mg/dL in men and ≥5.0 mg/dL in women) are lower than the previously reported values 10,11,17 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a similar trend was observed for cardiovascular mortality in both men and women, indicating the different threshold values of uric acid levels for mortality among men and women. Some previous studies reported the sex-specific threshold values of uric acid for all-cause mortality: uric acid levels ≥8.5 mg/dL in a male population in Japan (n = 49,413) 17 and Korea (n = 207,167) 11 and ≥7.5 mg/ dL in a female population in Korea (n = 167,996) 11 . The current study revealed that the threshold values of uric acid levels for all-cause mortality (≥7.0 mg/dL in men and ≥5.0 mg/dL in women) are lower than the previously reported values 10,11,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported the sex-specific threshold values of uric acid for all-cause mortality: uric acid levels ≥8.5 mg/dL in a male population in Japan (n = 49,413) 17 and Korea (n = 207,167) 11 and ≥7.5 mg/ dL in a female population in Korea (n = 167,996) 11 . The current study revealed that the threshold values of uric acid levels for all-cause mortality (≥7.0 mg/dL in men and ≥5.0 mg/dL in women) are lower than the previously reported values 10,11,17 . Similarly, a significant increase in the HR for cardiovascular mortality was detected at a lower value in the current study (≥7.0 mg/dL in men and 5.0-5.9 and ≥7.0 mg/dL in women) than in the previous study (≥9.5 mg/dL in men and ≥8.5 mg/dL in women) 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we comprehensively evaluated the contribution of genetic predisposition to hypouricemia with WES data and genotyping date in 81 unrelated patients. Our approach is derived from that of the previous population-based studies on the adverse health effects of hypouricemia 20,36 . Throughout our study, we were able to evaluate the genetic markers in hypouricemia which could have a potential diagnostic role for the first time.…”
Section: Discussionmentioning
confidence: 99%